Preliminary evaluation of a new clinical algorithm to interpret blood cultures growing coagulase-negative staphylococci. (July 2013) - Schnell, David; Lécuyer, Hervé; Geeraerts, Thomas; Dumenil, Anne-Sylvie; Bille, Emmanuelle; Mercier, Frédéric J.; Benhamou, Dan; Zahar, Jean-Ralph
Abstract Evaluating the clinical significance of blood cultures positive for coagulase-negative staphylococci (CoNS) is of critical importance since these microorganisms represent both the first contaminants of blood cultures and one of the leading causes of bloodstream infection (BSI). This prospective 2-centre study aimed to compare a previously reported algorithm to a clinical algorithm based on our experience. We identified 84 patients with CoNS-positive blood cultures. Twenty-seven (32%) were considered to have BSI according to our study algorithm. Thirty-seven (44%) patients were considered to have CoNS BSI according to the previously reported algorithm. The 2 algorithms isolated patients with similar rates of recurrences and hospital mortality. Our algorithm seemed to result in less diagnoses of CoNS BSI without harmful consequences compared to the previously reported algorithm. The impact on patient outcome and the inappropriate use of antibiotics deserves further investigation.